Validation of the Spanish version of the Oxford Cognitive Screen (S-OCS): psychometric properties of a short cognitive stroke-specific screening tool. (April 2019) - Valera-Gran, Desirée; López-Roig, Sofía; Hurtado-Pomares, Miriam; Peral-Gómez, Paula; García-Manzanares, María; Sunyer Catlla, Marta; Más Sesé, Gemma; Navarrete-Muñoz, Eva María; Sánchez-Pérez, Alicia
Objective: The aim of this study is to examine the psychometric properties of the Spanish version of the Oxford Cognitive Screen in a subacute stroke population. Participants and setting: Fifty-seven subacute stroke outpatients and 54 healthy individuals were recruited in Alicante province, Spain. Main measure: The Oxford Cognitive Screen. Other measures: The Montreal Cognitive Assessment, the Barcelona test, and the Barthel Index. Design: A validation study was conducted to analyze the inter-rater, intra-rater, test–retest, and internal consistency of the Spanish version of the Oxford Cognitive Screen. Concurrent validity was assessed using the Montreal Cognitive Assessment and the Barcelona test, and divergent validity using the Barthel index. Discriminant indices such as the sensitivity, specificity, predictive values, and optimal cut-offs were also estimated. Results: The subtests of the Spanish version of the Oxford Cognitive Screen showed excellent estimates for the inter-reliability (intraclass correlation coefficient (ICC) = 0.790 to 1.000; rs = 0.693 to 1.000), and acceptable-good for intra-reliability (ICC = 0.181 to 0.990) and test–retest reliability ( rs = 0.173 to 0.971). Internal consistency was also excellent (standardized Cronbach's α = 0.907). Spearman correlations for the concurrent validity were low-strong ( rs = −0.193 to 0.95) and low-moderate ( rs = −0.091 to 0.443) for divergent validity. The optimal cut-offs estimated for the subtests of the Spanish version of the Oxford Cognitive Screen showed good-high specificity (66.7%–100%) and positive predictive value (67.9%–100%), and low-good sensitivity (14.8%–83.3%) and moderate-good negative predictive value (53.5%–76.6%). Discriminant power as measured by the area under the curve indicated acceptable-good values (0.397 to 0.894). Conclusion: Our findings support that the Spanish version of the Oxford Cognitive Screen is a reliable and valid tool for screening cognitive impairments in subacute stroke patients.